Palladium-Alloy Membrane Reactors for Fuel Reforming and Hydrogen Production: A Review - Habib, Mohamed A; Harale, Aadesh; Paglieri, Stephen; Alrashed, Firas S; Al-Sayoud, Abduljabar; Rao, Manga Venkateswara; Nemitallah, Medhat A; Hossain, Shorab; Hussien, Muzafar; Ali, Asif; Haque, M. A; Abuelyamen, Ahmed; et al. (Energy & fuels, 2021)
Hydrogen has a potential to be a clean energy carrier that emits only water after combustion and can be produced from diverse feedstocks. Hydrogen has much better combustion characteristics in conventional combustion systems and higher energy efficiency when used with fuel cells. More than 75 million tons of hydrogen are currently produced primarily using fossil fuels as feedstock via steam methane reforming processes. Steam methane reforming is the mature technology for producing hydrogen and when coupled with CO2 capture can help address climate challenges. Inorganic palladium (Pd) membranes have demonstrated great potential to separate hydrogen due to their stability and high selectivity for hydrogen. In this review, several methods of fabricating Pd-alloy membranes are discussed and compared in terms of membrane stability and selectivity of hydrogen. Such methods include electroless plating (ELP), chemical vapor deposition (CVD), physical vapor deposition (PVD), and electroplating deposition (EPD). The permeability of hydrogen in different Pd-based alloy membranes are presented and compared. Focus has been made, in this review, on Pd–Ag, Pd–Cu, Pd–Au, and Pd–Ru alloys. The effects of impurities (H2S, CO, O2, and CO2) on performance of different Pd-based alloy membranes are also investigated. Moreover, the subject of using Pd-membrane reactors for fuel reforming and H2 production is investigated in detail based on numerous experimental and numerical studies in the literature, considering different membrane reactor designs: axial-flow tubular, radial-flow tubular, axial-flow spherical, packed-bed, fluidized bed, and slurry bubble column. The performance of Pd-membranes in such reactors for hydrogen production is compared, and the effects of temperature, pressure, H2O/CH4 ratio, and residence time on reformer performance are also investigated. Finally, the use of computational methods, particularly, density functional theory (DFT), to complement well-established experimental methods for studying the diffusion of H and its isotopes in different metals is reviewed. The review concludes with some insights into future work to bring Pd-membrane reactors to the level required for hydrogen production at the commercial level.